Trade-off between the resolutions of manufacture or purchase - a case study in the General Company for the manufacture of batteries - asfaad morthada saeed, (Iraqi Journal for Administrative Sciences, 2024)
he decision to manufacture or purchase one of the most important topics of business organizations today because of the challenges faced by these organizations, which necessitated her in looking for the best of the performance of its operations, whether Balsna within the organization or purchase by the external supplier. I felt the researcher and through Maashiha of the reality of production processes in the General Company for the manufacture of batteries, making the company the possibility of lead, which is the basic material in the manufacture of battery instead of buying from the external supplier. In order to test the effect of both options in the behavior of the production process, the researcher has designed two programs is the first study the behavior of the production process of manufacture in the case of either a second is studying the behavior of the production process in the case of purchase, using Monte Carlo simulation method of adoption of the Programme excel software. The results indicated preference made ​​on the purchase option and has therefore recommended that research material making bullets instead of purchase them from the external supplier.